6th International Symposium on Tonal Aspects of Languages (TAL 2018) 2018
DOI: 10.21437/tal.2018-20
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic correlates of word-accent in Basque

Abstract: Basque dialects differ substantially in their accentual properties. Previous work has focused mainly on phonological aspects of this prosodic diversity, such as the systems of rules for accent assignment. Less attention has been paid to variation in the acoustic realization of word-accent. Here we examine the realization of lexical accentual prominence in three different local varieties, which represent the three main Basque prosodic types: Azpeitia (in Gipuzkoa), Ondarroa (Northern Bizkaia) and Goizueta (Nava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 11 publications
2
11
0
1
Order By: Relevance
“…Summarizing, thus, this line of investigation on the effects of neutralization and word position on phonetic realization so far has produced the result that when word-final obstruents in VC#V have been analyzed as phonologically voiceless, they show greater reduction than other intervocalic instances of the same phoneme. This is what Hualde et al (2019) found for Basque /t k/. Some effect in this direction has also been reported for /s/ in Spanish, although in this case one cannot speak of a phonological contrast being suspended in word-final position.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…Summarizing, thus, this line of investigation on the effects of neutralization and word position on phonetic realization so far has produced the result that when word-final obstruents in VC#V have been analyzed as phonologically voiceless, they show greater reduction than other intervocalic instances of the same phoneme. This is what Hualde et al (2019) found for Basque /t k/. Some effect in this direction has also been reported for /s/ in Spanish, although in this case one cannot speak of a phonological contrast being suspended in word-final position.…”
Section: Introductionsupporting
confidence: 82%
“…The reason for stating this hypothesis is that, in word-final position, the contrast between the voiced and the voiceless series is neutralized, so that maintenance of contrast would not play a role in constraining the lenition in this position. Support for this hypothesis was found by Hualde et al (2019) based on a study of the realization of voiceless plosives in a corpus of Basque conversational data. As already mentioned, Basque, like Catalan, has a rule of word-final neutralization between voiced and voiceless plosives, in addition to sharing the "Iberian Spirantization" process (Mascaró 1991).…”
Section: Research Hypotheses and Methodsmentioning
confidence: 88%
“…The Basque varieties of Azpeitia, Lemoa, and Goizueta Basque have been previously studied with respect to other linguistic matters such as accentual systems (Hualde 1997), verbal morphology (Yrizar 1991, 1992, 2008), and lexical usage. Several dialectological studies mention Azpeitia Basque (Bonaparte 1869, Yrizar 1991), but only a few studies in recent years have attempted to give a more detailed phonological description of it (Hualde & Beristain 2017, 2018, 2019, 2020, Beristain 2018b, 2019). As far as Lemoa Basque is concerned, Gaminde (2002) and Gaminde et al (2013) have contributed to better understanding the phonological processes arising in varieties in that area.…”
Section: Methodsmentioning
confidence: 99%
“…Lujanbio’s (2016) doctoral dissertation examines linguistic variation within this town. There are also a number of studies concerned with the pitch accent system of Goizueta Basque including Hualde & Lujanbio (2008), Hualde, Lujanbio & Torreira (2008), Hualde & Beristain (2018), and Lujanbio (2018). Nonetheless, no study focusing on sibilants in three participant samples with different sibilant systems has been previously conducted, and this project will aim at addressing this gap in research.
Figure 1 Basque varieties under study.
…”
Section: Methodsmentioning
confidence: 99%
“…Posible izango lihttps://doi.org/10.1387/asju.22412 tzateke, hauetaz gain, beste faktore batzuk garrantzitsuak izatea, hala nola azentuaren kokagunea. Hala ere, orain arteko ikerketak erakutsi du intentsitateak ez duela balio handirik azentuaren ezaugarri akustiko bezala Azpeitiko euskaran (ikus Hualde & Beristain 2017, 2018.…”
Section: Irudiaunclassified